Human umbilical cord mesenchymal stem cells combined with porcine small intestinal submucosa promote the healing of full-thickness skin injury in SD rats - Xu XiaoMing; Chen Yan; Gu JiaMing; Liang LiTao; Zhang LiJuan; Song Ying; Yuan Lu; Song Qian; Dong Jian (Future Science OA)
Aim: To assess the therapeutic potential of human umbilical cord mesenchymal stem cells (hUCMSCs) combined with porcine small intestinal submucosa (SIS) on full-thickness skin injuries in rats. Methods: We established full-thickness skin injury models in Sprague–Dawley rats, dividing them into blank control, SIS, hUCMSCs and hUCMSCs combined with SIS. We monitored wound healing, scores and area, and analyzed inflammatory cells, microvessel density and collagen fibers after 12 days. Results: The blank group showed no healing, forming a scar of 0.6 × 0.5 cm2, while SIS and hUCMSCs groups exhibited incomplete healing with 0.4 × 0.5 cm2 scabs. Wound healing was significantly better in the hUCMSCs combined with the SIS group. Conclusion: Local application of hUCMSCs combined with SIS enhances full-thickness skin injury wound healing in rats.